EGS P06 Delays in Operating on General Surgery Patients Causes Increased Morbidity and Burden on the NHS. (7th December 2022) - Boag, Katie; Blow, Sophie; Mitchell, Thomas; Bassi, Vinod; Toogood, Giles; Peckham-Cooper, Adam
Abstract: Background: The number of patients waiting for an operation in the United Kingdom has never been higher, as of February 2022 over six million people were waiting for treatment. There is pressure nationally on trusts to implement strategies aimed at reducing the backlog of elective procedures. Long waiting lists can lead to a greater demand on acute surgical services as patients require treatment for their condition while they wait for their procedure. This study aims to determine the impact that long waiting lists have on patients, and how readmissions affect acute services in a busy tertiary General Surgical unit in England. Methods: Snapshot data was captured on a single day in February 2022 using the trust patient records system combined with the General Surgical waiting list. Data was collected and analysed in a bespoke excel data management tool built by the trusts patient costings team. The tool allows detailed analysis of patients readmitted whilst on the waiting list, outcomes and total cost. It also allows the data set to be explored as a whole and detailed patient level analysis. Wait time for emergency procedures was also analysed by length of pre-op and post-op stay. Results: A total of 2902 patients were awaiting a General Surgical procedure in February 2022, with an average wait of 34 weeks. 394 (14%) of these patients have attended acutely since being listed for elective surgery. The total cost implication of these reattendances is £563, 766. Analysis of a single procedure, such as laparoscopic cholecystectomy revealed 183 patients waiting for a cholecystectomy. 20% of these presented acutely, of which 68% was directly related to the listed underlying pathology with 34 bed days lost. 261 patients were awaiting a hernia (inguinal, umbilical, incisional) repair. 20% of these patients presented acutely whilst on the waiting list, with 33 lost bed days. Acute attendances increase as the waiting time increases; 38% of patients waiting over 15 months attend acutely, increasing to 50% at 22 months. Data from emergency procedures showed that as inpatient length of stay (LOS) pre-operatively increased in number of days, the post-operative LOS increased proportionally. Pre-op LOS of 1–2, 2–3, 3–4, 4–5, ≥5 led to post-op LOS of 2.9, 2.9, 4.2, 5.9 and 8.7 respectively. Conclusions: This study highlights that long waiting lists can lead to significant burden on acute General Surgical services as patients seek medical attention for the condition they are awaiting surgical management for, leading to costs of over half a million pounds. The problem becomes intensified by lost bed days due to these acute presentations, which can lead to cancelled elective procedures and pressure on acute surgical services. This results in emergency patients waiting longer in-hospital for an operation, who then have a longer post-operative LOS. Combined these findings suggest a higher morbidity for these patients. There is an urgent need for innovative strategies to reduce waiting lists, and increase theatre productivity. Data analysis tools like these allow trusts to nuance strategies to address these issues directly.